2003
DOI: 10.1089/107662903322541892
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Colonization byvanA- orvanB2-Containing Enterococcal Isolates of Healthy Animals in Spain

Abstract: Fecal samples of healthy animals (66 pigs, 22 pets) recovered during 1998 in La Rioja, Spain, were analyzed for vancomycin-resistant enterococci colonization. Vancomycin resistance mechanisms were analyzed by PCR and sequencing. vanA-containing enterococci were detected in 3 of 66 samples (4.5%) and 5 of 22 samples (22.7%) of the pig and pet samples, respectively. Seven unrelated pulsed-field gel electrophoresis (PFGE) patterns were detected among the 8 vanA isolates (7 Enterococcus faecium, 1 E. faecalis). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 40 publications
0
58
1
2
Order By: Relevance
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In recent years, different reports have alerted us to the spread of VRE and/or ESBL-containing E. coli isolates from clinical, farm and wild animals in different European countries (Mallon et al, 2002;Torres et al, 2003;Bonnedahl et al, 2010;Literak et al, 2010;Pinto et al, 2010). Although the percentage of vanA isolates from wild birds in the Azores was lower when compared with other studies performed in mainland Portugal in farm and wild animals (Poeta et al, 2005a;Gonçalves et al, 2010;Radhouani et al, 2010b, Radhouani et al, 2010c, our isolates showed a phenotype of multi-resistance.…”
Section: Discussionmentioning
confidence: 45%
“…The isolates with resistance to one or more antimicrobials were selected for antimicrobial-resistance gene characterization. In VRE isolates, the vancomycin resistance genes (vanA, vanB, vanC-1, and vanC-2) were tested by PCR (Torres et al, 2003) in all enterococcal isolates that showed resistance or reduced susceptibility to glycopeptides. The resistance genes for the other studied antimicrobials were also tested by PCR and were: erm(A), and erm(B) (in erythromycin-resistant isolates) (Torres et al, 2003); tet(M) and tet(L) (in tetracycline-resistant isolates) (Aarestrup et al, 2000;Torres et al, 2003); vat(D) and vat(E) (in quinupristin/dalfopristinresistant isolates) (Aarestrup et al, 2000); and aph(3?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance genes were sought by PCR in enterococcal isolates that showed resistance to glycopeptides (van(A), van(B), van(C1), and van(C2)) [16]…”
Section: Antimicrobial Susceptibility Testing and Detection Of Resistmentioning
confidence: 99%
“…Para a realização da detecção dos genes de resistência por PCR, foram utilizadas colônias isoladas conforme descrito por Titze-de-Almeida et al (2004). Para a identificação dos genes de resistência aos antimicrobianos, foram utilizados os primers vanA, vanB, vanC-1 e vanC-2/3 para Vancomicina; os primers ant(6)-Ia, aac(6')-Ie-aph(2'')-Ia e aph(3')-IIIa para Aminoglicosí-deos; os primers erm(A), erm(B), erm(C) para Macrolídeos; e o primer tet(M) para Tetraciclina (Torres et al, 2003). As condições para a realização da PCR-multiplex para detecção dos genes de resistência à Vancomicina foram as mesmas utilizadas na diferenciação das espécies E. faecium e E. faecalis.…”
Section: Methodsunclassified